2020
DOI: 10.1016/j.agrformet.2019.107791
|View full text |Cite
|
Sign up to set email alerts
|

Improving RAMS and WRF mesoscale forecasts over two distinct vegetation covers using an appropriate thermal roughness length parameterization

Abstract: Land Surface Models (LSM) have shown some difficulties to properly simulate day-time 2-m air and surface skin temperatures. This kind of models are coupled to atmospheric models in mesoscale modelling, such as the Regional Atmospheric Modeling System (RAMS) and the Weather Research and Forecasting (WRF) Model. This model coupling is used within Numerical Weather Prediction Systems (NWP) in order to forecast key physical processes for agricultural meteorology and forestry as well as in ecological modelling. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The Advanced Research core of the WRF model (WRF-ARW) [20,21], version 3.6.1 (Boulder, CO, USA), was used to simulate the selected forecasting period: 6 to 11 July 2011. The model setup is based on that used in previous studies [6,28] conducted over the study area. WRF was set up using the Dudhia shortwave radiation [35] and the rapid radiative transfer model (RRTM) longwave radiation [36] as radiation options, whereas the YSU scheme [37] was used as the PBL parameterization.…”
Section: Numerical Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…The Advanced Research core of the WRF model (WRF-ARW) [20,21], version 3.6.1 (Boulder, CO, USA), was used to simulate the selected forecasting period: 6 to 11 July 2011. The model setup is based on that used in previous studies [6,28] conducted over the study area. WRF was set up using the Dudhia shortwave radiation [35] and the rapid radiative transfer model (RRTM) longwave radiation [36] as radiation options, whereas the YSU scheme [37] was used as the PBL parameterization.…”
Section: Numerical Setupmentioning
confidence: 99%
“…Accurate and reliable information of surface energy fluxes and atmospheric variables is of critical importance for different application fields, not only for atmospheric and climate modeling but also for agricultural, ecological, and hydrological purposes, among others. One of the efforts focused on improving the simulation of surface energy fluxes and atmospheric variables has been dedicated to an accurate simulation of land surface and atmosphere interactions [1][2][3][4][5][6][7]. All these studies have shown essential synergies between the land surface and the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the difference of summer ΔT in North China between the Czil-h and default M-O schemes is 1.48 °C, in which the mean bias for Ts is 1.28 °C (the contribution of 86.49%) and for Ta is -0.20 °C. These demonstrate the important role of Ch in controlling Ts, andYang et al (2011) indicated that Ch is the most important factor of modeling Ts, thus, considerable efforts by the LSMs modelers have been spent to improve the performance of model in reproducing Ts through the Ch parameterization(Chen et al 2011;Gomez et al 2020).Discussions 4.1 Sensitivities of surface flux and precipitation simulations to the Czil-h scheme and the uncertainties of applying the Czil-h scheme…”
mentioning
confidence: 97%